Inventário, quantificação e mapeamento de geomorfossítios em Tibau, Grossos e Areia Branca/RN - Terto, Maria Luiza de Oliveira (2021)
Geodiversity is a recent concept associated with the abiotic elements of nature, related to the term biodiversity, which is more debated in the academic and social spheres. In this work, geodiversity will be discussed through the apprehension of geomorphological elements, forming geomorphodiversity, which, applied to the coastal environment, stands out with the potential to identify singular forms, which are areas of geoconservation actions. In this sense, the present work aims to outline the objective of geoconservation through the inventory, quantification and mapping of geoforms on the coast of Tibau, Grossos and Areia Branca / RN, also seeking to describe the evolution of the natural history of the geoforms in the area. In the present study, possible geomorphosites were identified, through the steps, evidence and quantification. In the field inventory, a survey of general information of the sites was carried out, involving the geomorphology, dissection features, among others, consolidating a database for the studied area. In the quantification, an offer of areas of interest was valued using four value criteria: Aesthetic (VEst), Scientific (VCi), Tourism (VTur) and Use and management (VUG). In this study, it was identified as geomorphosite those that obtained high scores in the Scientific Value (VCi) and/or Aesthetic Value (EST), namely: Apodi Mossoró Estuary, São Cristóvão Beach and Ponta do Mel Beach. Those that obtained high scores in Tourism Values, Use and Management and/or Average scores in Aesthetic and Scientific values considered as geomorphodiversity sites, namely: Pedra do Chapéu, Praia da Barra and Upanema Beach. Through the obtained results, it is pertinent the inclusion of the aesthetic criterion, and not only the scientific one, for the identification of geomorphosites. We found that there are areas with high aesthetic value, but with reduced representation of scientific value, due to the lack of scientific research in the field of geosciences covering them. Corroborating the view that the aesthetic potential is representative for society and therefore must be included in geoconservation actions.